THE EFFECT OF RESPONSIBILITY ACCOUNTING IMPLEMENTATION ON MANAGERIAL PERFORMANCE - Lestari, Rini; Aryana, Salman (UPT Publikasi Ilmiah UNISBA, 2024)
Most organizations must be able to keep up with all the progress in order to achieve a goal, so adequate managerial performance is needed. The variables that can affect organizational performance with the application of Accountability Accounting so that the organization can achieve its objectives effectively and efficiently. The purpose of this study was to determine the effect of the application of Accountability Accounting on managerial performance at Amil Zakat Institutions in Bandung City and Cimahi City. This research method uses a descriptive method with a quantitative approach. The primary data sources used data obtained from managers of Amil Zakat Institutions in Bandung City and Cimahi City. The research sampling technique used nonprobability sampling with convenience sampling technique and received a sample of 61 respondents. The analytical tool used in this research is SmartPLS version 3.2.9. The results of this study indicate that the application of accountability accounting affects managerial performance. Keywords : Managerial Performance, Responsibility Accounting Implementation.